2020
DOI: 10.1002/ehf2.13129
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent changes in plasma xanthine oxidoreductase during hospitalization of acute heart failure

Abstract: Aims The aim of present study is to evaluate the clinical significance of the time-dependent changes in xanthine oxidoreductase (XOR) activity during hospitalization for acute heart failure (AHF). Methods and results A total of 229 AHF patients who visited to emergency room were prospectively enrolled, and 187 patients were analysed. Blood samples were collected within 15 min of admission (Day 1), after 48-72 h (Day 3), and between Days 7 and 21 (Day 14). The AHF patients were divided into two groups according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…10,11) Their technique enables the stable measurement of tiny amounts of human XOR activity in vivo. 9) Between 2019 and 2021, we have presented numerous lines of evidence regarding human XOR activity, such as in patients with AHF, recruited from out-patients clinics, and critically ill. [3][4][5][6][7] XOR produces ROS that might induce organ dysfunction. A previous study showed that a certain level of XOR was expressed on the vascular endothelium, wherein XO binds to glycosaminoglycan residues as a consequence of tissue damage such as ischemia and inflammation.…”
Section: Subjectsmentioning
confidence: 99%
See 4 more Smart Citations
“…10,11) Their technique enables the stable measurement of tiny amounts of human XOR activity in vivo. 9) Between 2019 and 2021, we have presented numerous lines of evidence regarding human XOR activity, such as in patients with AHF, recruited from out-patients clinics, and critically ill. [3][4][5][6][7] XOR produces ROS that might induce organ dysfunction. A previous study showed that a certain level of XOR was expressed on the vascular endothelium, wherein XO binds to glycosaminoglycan residues as a consequence of tissue damage such as ischemia and inflammation.…”
Section: Subjectsmentioning
confidence: 99%
“…We also found that patients in whom high XOR activity was prolonged despite optimal therapy tended to have poor outcomes during AHF treatment. 7) If the AHF was not sufficiently compensated, the unstable hemodynamics would continue despite appropriate treatment/support, which would subsequently induce high XOR activity and adverse outcome. Moreover, we determined that high XOR activity led to high in-hospital mortality in the critically-ill patients.…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations